2011
DOI: 10.1093/jpepsy/jsr086
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Child Interaction Therapy as a Family-Oriented Approach to Behavioral Management Following Pediatric Traumatic Brain Injury: A Case Report

Abstract: This case demonstrates the feasibility of using PCIT with a child older than the recommended age range to address behavior problems associated with TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Overall, these findings suggest that parent–child interactions may be affected in the first several months following a TBI, particularly following a complicated mild/moderate TBI. As indicated, previous evidence suggests that levels of warm responsiveness and negativity are associated with short-term behavioral outcomes in pediatric TBI (Wade et al, 2011), and recent studies document improved behavioral outcomes from teaching positive parenting skills (Cohen et al, 2012; Wade et al, 2009). The question emerges whether this study demonstrates a resolution of the negative effects of TBI over time, at least for the complicated mild/moderate TBI group, or perhaps an obscuring of the effect in the context of social desirability or normative decreases in positive parenting interactions.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Overall, these findings suggest that parent–child interactions may be affected in the first several months following a TBI, particularly following a complicated mild/moderate TBI. As indicated, previous evidence suggests that levels of warm responsiveness and negativity are associated with short-term behavioral outcomes in pediatric TBI (Wade et al, 2011), and recent studies document improved behavioral outcomes from teaching positive parenting skills (Cohen et al, 2012; Wade et al, 2009). The question emerges whether this study demonstrates a resolution of the negative effects of TBI over time, at least for the complicated mild/moderate TBI group, or perhaps an obscuring of the effect in the context of social desirability or normative decreases in positive parenting interactions.…”
Section: Discussionmentioning
confidence: 89%
“…Presumably, enhancing parental warm responsiveness could result in improved behavioral outcomes, particularly among those at increased risk for behavior problems. Emerging research has begun demonstrating that teaching positive parenting skills improves behavioral outcome in children with a TBI (Cohen, Heaton, Ginn, & Eyberg, 2012; Wade, Oberjohn, Burkhardt, & Greenburg, 2009), although more research is clearly needed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…An example of an established treatment that may emerge as a treatment for a TBI cohort includes parent-child interaction therapy (PCIT) [95]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is unclear whether intervention effects will continue to maintain over time. However, relative to other intervention studies for children with TBI that only reported post-intervention data (Antonini et al, 2014(Antonini et al, , 2012Cohen et al, 2012), the current study provides preliminary support for maintenance of intervention gains. Lastly, the current study was primarily conducted in a university-based clinic setting, with home-based intervention delivery for two families.…”
Section: Study Limitationsmentioning
confidence: 45%
“…Results indicated improvements in behavioral outcomes and parental distress associated with the child's behavior (Cohen, Heaton, Ginn, & Eyberg, 2012). However, post-intervention findings were derived solely from parent report of the frequency of problem behaviors, the extent to which parents found the behaviors problematic, and qualitative observations.…”
Section: Family-focused Interventions For Young Children With Tbimentioning
confidence: 99%